Аналіз сформованості компонентів готовності до професійного спілкування у майбутніх іноземних спеціалістів-медиків - Рагріна, Жанна Михайлівна; Рагрина, Ж. М.; Ragrina, Z. (Класичний приватний університет, 2017)
У статті розкрито дефініції підготовки та готовності майбутніх іноземних спеціалістів-медиків до професійного спілкування. Проаналізовано структуру комунікативної готовності майбутніх іноземних спеціалістів-медиків, яка складається з мотиваційного, діяльнісно-змістового, комунікативного та результативного компонентів. Надано порівняльну характеристику рівнів сформованості у майбутніх іноземних спеціалістів-медиків готовності до професійного спілкування на різних етапах педагогічного експерименту. В статье раскрыты дефиниции подготовки и готовности будущих иностранных специалистов-медиков к профессиональному общению. Проанализирована структура коммуникативной готовности будущих иностранных специалистов-медиков, которая состоит из мотивационного, деятельностно-смыслового, коммуникативного и результативного компонентов. Предоставлена сравнительная характеристика уровней сформированности у будущих иностранных специалистов-медиков готовности к профессиональному общению на разных этапах педагогического эксперимента. The article is devoted to the problem of professional preparation in the medical universities. It reveals the definitions of the preparation and readiness of the future foreign medical professionals for the professional communication. In the pedagogical theory the term “readiness” is considered as an integrative, professionally significant quality of the individual, which is a system of interconnected structural components that contains personal (professional motives and interests) and procedural (professional knowledge and skills) aspects. The readiness for the professional communication is understood by scientists as a property of the individuals that promotes the objectives of professional activity by sharing information. The structure of the communicative readiness of the future foreign medical professionals is also analyzed. The researcher concretizes that it consists of motivational, activity-semantic, communicative and effective components. According the components the criteria and levels of forming the preparedness of future foreign medical professionals for professional communication are determined. The researcher emphasizes that there is necessary to consider the criteria and indicators of the foreign medical students’ readiness for the professional communication from the point of intersection of psychology, pedagogy and linguistics. The comparative description of levels of foreign medical students’ readiness for professional communication at the beginning and at the end of the experimental teaching was conducted and described in the research. The indicators demonstrate positive dynamics in the experimental group: quantitative indicators of each component indicate qualitative changes in the formation of readiness of foreign medical students for professional communication. Moreover the author underlines that the foreign medical students’ readiness for the professional communication can provide its competitiveness as a future professionals. The professional competitiveness is also one of the reason of the formation and development of foreign medical students’ motivation for the language learning.
Анализ сформированности компонентов готовности к профессиональному общению у будущих иностранных специалистов-медиков
Analysis of the Components’ Formation of the Future Foreign Medical Specialists’ for Professional Communication
Keywords: готовність до професійного спілкування; майбутні іноземні спеціалісти-медики; професійна комунікація; професійно орієнтована мовленнєва підготовка; формування; готовность к профессиональному общению; будущие иностранные специалисты-медики; профессиональная коммуникация; профессионально ориентированная языковая подготовка; формирование; readiness for professional communication; future foreign medical specialists; professional communication; professionally oriented language training; formation